Betacyanins and Anthocyanins in Pulp and Peel of Red Pitaya (Hylocereus polyrhizus cv. Jindu), Inhibition of Oxidative Stress, Lipid Reducing, and Cytotoxic Effects - Khoo, Hock Eng; He, Xuemei; Tang, Yayuan; Li, Zhichun; Li, Changbao; Zeng, Yuan; Tang, Jie; Sun, Jian (Frontiers in Nutrition, 2022)
This study aimed to promote red pitaya fruit parts as alternate sources of nutraceuticals. The red pitaya of Chinese origin was determined for its in vitro efficacy, where the fruit extracts were evaluated based on the selected antioxidative properties, lipid-reducing capacity, and cytotoxicity. The betanin, total betacyanins, total anthocyanins, and DPPH radical scavenging activity of the red pitaya pulp and peel extracts were determined by spectrophotometric analyses. Cell culture assays were used to examine in vitro efficacy and cytotoxicity of the pitaya extracts. The result showed that red pitaya peel extract had a higher total betacyanins and total anthocyanins content than the pulp extract, but the peel extract had a lower DPPH radical scavenging effect than the pulp extract. The red pitaya extracts also had a protective effect in reducing oxidative stress, especially the peel extract. All fruit samples had a low anticancer potential except for betanin and anthocyanin standards. The protective effect of pitaya peel could be attributed to betacyanins and anthocyanins. Both pulp and peel extracts had a weak anticancer effect because these extracts contained polysaccharides and other phytochemicals that were not cytotoxic. As the peel extract of red pitaya was not cytotoxic, it is a potent source of betacyanins for reducing oxidative stress.